PRESUPPOSITION OF FOOD ADVERTISEMENT IN INSTAGRAM - Romarsauli Feriranto Sitompul; Festi Kristina Sarumaha; Hiace Vega Fernando Siahaan (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This research deals with Presupposition of Food Advertisement in Instagram. The objectives of the research are to find out the types of presupposition, the most dominant type of presupposition in food advertisement. This study was conducted by using descriptive qualitative method. The object of the study is presupposition of food advertisement in Instagram. This study implemented applying documentary technique. After doing the analysis, the writer found that there were 2 types of presupposition. The data were collected as many as 47 data which consist 29 of existential presupposition and counterfactual presupposition as many as 18 data. The analysis found that the existential presupposition is the dominant types to state presupposition of food advertisement in instagram. The reason why existential presupposition is the dominant types for 47 data of food advertisement in Instagram because most of the advertisement assumed to be present in possessive contraction or any definite noun phrases attached to the sentence and assumed the thing is exist, based on Yule’s theory Existential presupposition it is the assumption of the existence of the entities named by the speaker.